2011
DOI: 10.1128/jmbe.v12i1.272
|View full text |Cite
|
Sign up to set email alerts
|

Gain in Student Understanding of the Role of Random Variation in Evolution Following Teaching Intervention Based on Luria-Delbruck Experiment

Abstract: Undergraduate students in introductory biology classes are typically saddled with pre-existing popular beliefs that impede their ability to learn about biological evolution. One of the most common misconceptions about evolution is that the environment causes advantageous mutations, rather than the correct view that mutations occur randomly and the environment only selects for mutants with advantageous traits. In this study, a significant gain in student understanding of the role of randomness in evolution was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 11 publications
1
32
1
Order By: Relevance
“…There are indications that threshold concepts include abstract concepts that are not necessarily specific to natural selection, but vital for grasping its principles, and these concepts must be pointed out in parallel with the key concepts of natural selection. Concepts that may hinder the learning of natural selection include temporal scale (Catley and Novick 2009;Cheek 2012), spatial scale (Kalinowski et al 2010), probability, and randomness (Garvin-Doxas and Klymkowsky 2008; Mead and Scott 2010;Robson and Burns 2011). Ross et al (2010) have also proposed several biological concepts that they distinguish from being only biological concepts because they concern more fundamental and general aspects of natural science.…”
Section: Threshold Concepts For Understanding the Principles And Key mentioning
confidence: 99%
See 1 more Smart Citation
“…There are indications that threshold concepts include abstract concepts that are not necessarily specific to natural selection, but vital for grasping its principles, and these concepts must be pointed out in parallel with the key concepts of natural selection. Concepts that may hinder the learning of natural selection include temporal scale (Catley and Novick 2009;Cheek 2012), spatial scale (Kalinowski et al 2010), probability, and randomness (Garvin-Doxas and Klymkowsky 2008; Mead and Scott 2010;Robson and Burns 2011). Ross et al (2010) have also proposed several biological concepts that they distinguish from being only biological concepts because they concern more fundamental and general aspects of natural science.…”
Section: Threshold Concepts For Understanding the Principles And Key mentioning
confidence: 99%
“…Following reports of students' difficulties by various authors, we concluded that probability and randomness are threshold concepts for understanding natural selection (e.g., Mead and Scott 2010;Robson and Burns 2011). These difficulties appear to be rooted in deep-seated misconceptions about random processes, which may lead people (inter alia) to interpret unusual coincidences as paranormal because they misunderstand the probability of their occurring by chance (Paola 2002).…”
Section: Randomness and Probabilitymentioning
confidence: 99%
“…Thus, bacteria provide teachers with an opportunity to demonstrate evolutionary processes in large populations within a school laboratory in real time (Elena & Lenski, 2003;Smith et al, 2015). Researchers have found that these kinds of laboratory set-ups are associated with the successful teaching of evolution (Krist & Showsh, 2007;Delpech, 2009;Robson & Burns, 2011;Serafini & Matthews, 2009), although exact reasons for increased student scores when learning about evolution through bacterial contexts still remain to be explained.…”
Section: Evolution In Light Of Antibiotic Resistancementioning
confidence: 99%
“…Among these are that mutations are always harmful (Cho, Kahle & Nordland, 1985) and that evolution is driven by the needs of an organism (Bizzo, 1994). Consequently, Robson and Burns (2011) found interventions that directly target students' understanding of randomness in mutations to enhance learning and comprehension.…”
Section: Fig 21mentioning
confidence: 99%
See 1 more Smart Citation